2016
DOI: 10.1016/j.applanim.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of Qualitative Behaviour Assessment as an indicator of welfare in donkeys

Abstract: One of the objectives of the Animal Welfare Indicators project was to develop animal-based indicators to assess donkey welfare, including their emotional state. This study aimed to develop a fixed rating scale of Qualitative Behaviour Assessment (QBA) for donkeys, to evaluate the inter-observer reliability when applied on-farm, and to assess whether the QBA outcomes correlate to other welfare measures.A fixed list of 16 descriptors was designed on the basis of a consultation in a focus group. The fixed list wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 28 publications
4
87
2
1
Order By: Relevance
“…Inter-observer reliability with regard to QBA has two aspects: agreement in qualitative ranking of animals on expressive dimensions, and agreement in mean value of animal scores on expressive dimensions [43]. Agreement on qualitative ranking in the present study was good for all four PCs, (W=0.60-0.80), which aligns with previous studies testing the reliability of QBA fixed lists in a range of species [25,44,45], though some recent studies indicate that in field conditions as opposed to video-based conditions, achieving good agreement on qualitative ranking of animals on QBA dimensions can be more difficult [45,46]. There was however a significant observer effect on the mean value of animal scores for all four PCs suggesting differences between observers in how they used VAS scales for scoring across most terms.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Inter-observer reliability with regard to QBA has two aspects: agreement in qualitative ranking of animals on expressive dimensions, and agreement in mean value of animal scores on expressive dimensions [43]. Agreement on qualitative ranking in the present study was good for all four PCs, (W=0.60-0.80), which aligns with previous studies testing the reliability of QBA fixed lists in a range of species [25,44,45], though some recent studies indicate that in field conditions as opposed to video-based conditions, achieving good agreement on qualitative ranking of animals on QBA dimensions can be more difficult [45,46]. There was however a significant observer effect on the mean value of animal scores for all four PCs suggesting differences between observers in how they used VAS scales for scoring across most terms.…”
Section: Discussionsupporting
confidence: 88%
“…Most QBA studies report differences in the level of agreement with which various individual terms were applied by observers (e.g. [25]) In the present study 12 out of 20 individual descriptors were applied at a level of agreement lower than 0.60, while 3 terms (depressed, explorative, aggressive) fell below 0.50. This lack of agreement may to some extent be due to the relatively low prevalence of these expressions in the video clips, however depressed demeanour may generally be difficult to distinguish reliably from other low energy expressions such as relaxed and/or bored [29,47].…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…There are welfare assessment tools available for individual and group assessment of donkey welfare such as animal welfare indicators (AWIN) welfare assessment protocol for donkeys and, for working donkeys, the standardised equine-based welfare assessment tool (SEBWAT) (see further reading). There are also almost continual advances in animal behaviour science, such as qualitative behaviour assessment (QBA), looking at the emotional state of the donkey (Minero and others 2016). …”
Section: How To Assess Quality Of Lifementioning
confidence: 99%
“…Furthermore, a similar qualitative approach -Qualitative Behavior Assessment (QBA; Wemelsfelder et al, 2000) -was developed to assess welfare in farm animals and has been shown to be a valid and reliable method in swine (Wemelsfelder et al, 2000), dairy cattle (Rousing and Wemelsfelder, 2006), beef cattle , dairy buffalo (Napolitano et al, 2012), sheep (Phythian et al, 2013), and donkeys (Minero et al, 2015). Despite the vast literature employing rating methods to assess temperament of captive wild animals, these methods have rarely been used to assess the temperament of farm species.…”
Section: Introductionmentioning
confidence: 99%